The Relationship between Earnings Quality and Audit Quality: An Iranian Angle - Mohammad Seddigh Ansari Qeshmi; Hamideh Nazaridavaji (Iranian Journal of Accounting, Auditing & Finance)
The present study is concerned about the relationship between earnings quality and audit quality of audit firms to figure out whether the earnings quality of firms audited by larger audit firms is more than that of the smaller firms or the earnings quality of firms audited by longer tenure audit firms is more than that of the shorter tenure firms or not.The study's hypotheses were tested using a sample of 129 year-company listed on the Tehran Stock Exchange during 2012-2016 and by using the multiple regression pattern based on the data integration technique. Hence, the multivariable regression model is used for testing the hypotheses.The obtained results show that the earnings quality of firms audited by small audit firms outweighs that of the large audit firms. Moreover, the findings indicate that those firms audited by longer tenure audit firms, compared with those audited by shorter tenure audit firms, enjoy a better earnings quality.